Dream analysis and counseling live demonstrations - Microtraining Associates ([Framingham, Mass.] : Microtraining Associates, 2004)
Describes Allen Ivey's Developmental Counseling Therapy (DCT) model, applies DCT to dream interpretation, and conducts dream analysis
Title from title screen
Keywords: Cognitive therapy -- Methods; Dreams